The application of POSS nanostructures in cartilage tissue engineering: the chondrocyte response to nanoscale geometry. (10th April 2013) - Oseni, Adelola O.; Butler, Peter E.; Seifalian, Alexander M.
Abstract: Despite extensive research into cartilage tissue engineering (CTE), there is still no scaffold ideal for clinical applications. Various synthetic and natural polymers have been investigated in vitro and in vivo, but none have reached widespread clinical use. The authors investigate the potential of POSS–PCU, a synthetic nanocomposite polymer, for use in CTE. POSS–PCU is modified with silsesquioxane nanostructures that improve its biological and physical properties. The ability of POSS–PCU to support the growth of ovine nasoseptal chondrocytes was evaluated against a polymer widely used in CTE, polycaprolactone (PCL). Scaffolds with varied concentrations of the POSS molecule were also synthesized to investigate their effect on chondrocyte growth. Chondrocytes were seeded onto scaffold disks (PCU negative control; POSS–PCU 2%, 4%, 6%, 8%; PCL). Cytocompatibilty was evaluated using cell viability, total DNA, collagen and GAG assays. Chondrocytes cultured on POSS–PCU (2% POSS) scaffolds had significantly higher viability than PCL scaffolds ( p < 0.001). Total DNA, collagen and sGAG protein were also greater on POSS–PCU scaffolds compared with PCL ( p > 0.05). POSS–PCU (6% and 8% POSS) had improved viability and proliferation over an 18 day culture period compared with 2% and 4% POSS–PCU ( p < 0.0001). Increasing the percentage of POSS in the scaffolds increased the size of the pores found in the scaffolds ( p < 0.05). POSS–PCU has excellent potential for use in CTE. It supports the growth of chondrocytes in vitro and the POSS modification significantly enhances the growth and proliferation of nasoseptal chondrocytes compared with traditional scaffolds such as PCL. Copyright © 2013 John Wiley & Sons, Ltd.